Practicum Ticker Timer with Inquiry Approach to Improve Student Learning Outcomes - Nur Khoiri; Sintia Respayanti; Affandi Faisal Kurniawan; Sigit Ristanto (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop a ticker timer practicum guide with an inquiry approach to improve student learning outcomes in class X MIPA. This research was conducted at SMAN 1 Belik Pemalang with the research subjects being all students of class X MIPA 1 and X MIPA 2 SMAN 1 Belik Pemalang. The research method used is Research and Development. Data collection techniques through tests and observations. The results of the study showed that (1) the ticker timer practicum guide in terms of material and media content shows the practicum guide in the "Very Good" criteria and is suitable for use with an average score of 90% material validation and 92% media. (2) the ticker timer practicum guide with an inquiry approach to improve student learning outcomes, there is a difference in the acquisition of the N-Gain score for the experimental class <G> = 0.68 in the medium category and the control class <G> = 0.30 in the medium category. Thus, it can be concluded that the development of a ticker timer practicum guide with an inquiry approach can improve student learning outcomes but not too significantly